A three-dimensional numerical model of unsteady flow and heat transfer in ceramic honeycomb regenerator. (5th September 2016) - You, Yonghua; Huang, Huang; Shao, Guiwei; Hu, Ji; Xu, Xuecheng; Luo, Xiaobing
Highlights: 3D numerical simulation is conducted on honeycomb regenerator for a better precision. Heat transfer mechanism is analyzed by temperature contours at different moments. Effects of length and switch time on flow and heat transfer performances are studied. Optimal regenerator length is 300 mm based on the comprehensive behaviors. Abstract: Honeycomb regenerators are widely used in regenerative burners to preheat combustion air with exhausted flue gases and their unsteady conjugated heat transfer were investigated by two-dimensional numerical simulations in the literatures. In the present work, a three-dimensional numerical model is constructed with the CFD package ANSYS Fluent for the ceramic honeycomb regenerator with small square openings. In this model, the Navier-Stokes equations are solved for the fluid velocity and user-defined functions are compiled to express the alternate flow of air and flue gas in the opposite directions. To minimize the computation load, the unit cell is taken to stand for the whole device and the radiation heat transfer is ignored. The numerical model is validated by comparing the computed results with the numerical and experimental data released in the literature. With the current numerical investigation, the heat transfer mechanism in the regenerator is analyzed, and the effects of regenerator length and switching time on the performances of heat transfer and flow resistances are investigated under the conditions of different fluid flowrates.